수도권 거주환자의 구강건강인식과 그 연관요인 - 정의정; Ui Jung Jung; 김민영; Min Young Kim (Chiwisaeng gwahakoeji, 2007)
The purpose of this study was to analyze the effects of dentistry users' perception of concern about oral health on their perception of oral health and behaviors. For this purpose, the researcher sampled the outpatients who had used 2 dentistries in Kangnam, Seoul and another 2 dentistries in Kangbuk, Seoul and a hospital attached to a dental college in Bundang, Kyonggi-do and thereby, conducted a self-administered questionnaire survey from April 4 through 28, 2006. 291 responses from the survey were analyzed using the SPSS 12.0 statistical program. The results of this study can be summarized as follows; 1. 45.0% of the patients perceived that their oral conditions were not healthy, 32% thought normal for their oral conditions and 23% felt healthy for their oral conditions. 2. Less women (44.1%) felt healthy for their oral conditions than men (46.3%). 3. The more negative patients' perception of their oral health was, they were more likely (55.1%) to rely on relatives for choice of a dentistry. 45.0% of this group worried about their oral health always, 15.1% were more or less worried, and 11.9% of them felt that their oral health was good(P < 0.05). 4. 66.0% of the subjects worried about their oral health sometimes, and 27.8% of them worried always, and 6.2% worried little. There was no significant gender difference, but the older they were, they worried more always(P < 0.05). 5. 93.8% of the group who worried about their oral health always had ever had their teeth scaled, and 65.8% of them had regularly had their teeth scaled. Such ratios differed significantly from the group who worried about their oral health sometimes (49.7% and 46.2%, respectively). The three groups differed in terms of regular checks significantly: 56.6%, 45.3% and 33.3%, respectively. And the rate of visiting the dentistry without fail was significantly highest (71.6%) in the first group (P < 0.05). 본 연구에서는 구강건강인식과 구강건강염려가 구강보건인식 및 스켈링 행태에 어떠한 영향을 미치는가를 알아보고자 하였다. 이를 위해 조사대상은 서울 강남에 위치한 치과의원 2개소와, 강북에 위치한 2개소, 분당지역의 치과대학부속병원을 내원한 만 18세 이상 환자들을 대상으로 하였으며, 2006년 4월 5일부터 4월 28일까지 자기기입식 설문조사를 실시하고, 291부를 SPSS 12.0 통계프로그램을 이용하여 분석하였다. 이에 그 결과를 분석한 바, 다음과 같은 결론을 얻었다. 1. 자신의 구강상태를 건강하지 않다고 인식한 비율이 45.0%로 가장 높았고, 성별에 따라서는 여성(44.1%)에 비해 남성(46.3%)이 건강하지 못하다고 인식하는 비율이 조금 높았다. 2. 자기구강건강인식이 부정적 일수록 진료기관 선택을 친지 등의 권유(55.1%)에 의존하는 비율이 높았고, 구강건강염려정도는 항상 걱정한다는 응답률이 45.0%로 보통(15.1%)이거나 건강한 편(11.9%)이라고 인식하는 대상자와 유의한 차이를 보였다(P < 0.05). 3. 자기구강건강인식에 따른 잇솔질 횟수는 매식 후 3회 응답률이 건강한 편이 44.8%, 보통이 47.3%, 건강하지 못한 편이 41.2%로 큰 차이가 없었으나 4회 이상은 건강한 편이 26.9%로 가장 높았고, 보통이 9.7%, 건강하지 못한 편이 15.3%로 유의한 차이를 보였다. 4. 구강건강염려정도는 가끔 걱정함이 66.0%로 가장 높았고, 남녀차이는 유의하지 않았으나 연령별로는 연령이 높아질수록 항상 걱정함의 응답률이 유의하게 높아졌다(P < 0.05). 5. 구강건강염려정도가 '항상 걱정함'인 응답자 93.8%가 스켈링 경험이 있었고, 그 중 정기적인 스켈링을 하는 대상자는 65.8%로 '가끔 걱정함' 49.7%, '걱정하지 않음' 46.2%와 유의한 차이를 보였으며, 정기검진을 받고 있는 대상자도 55.6%로 '가끔 걱정함' 45.3%, '걱정하지 않음' 33.3%보다 높았다. 또한 아플 경우 미루지 않고 치과병의원을 내원하는 율도 71.6%로 유의한 차이를 보였다(P < 0.05). 고령화 사회로 진입한 현실에서 구강건강의 중요성과 삶의 질에 미치는 영향에 대한 인식이 증가되고 있다. 이에 실질적인 국민의 구강건강관련 삶의 질 증진을 위해 구강건강인식도를 적극 활용하여 치과치료의 필요도를 탐색하거나, 치료의 평가에 적극 활용함이 필요하다고 여겨진다.